Effect of preparation design on marginal adaptation and fracture strength of ceramic occlusal veneers: A systematic review - Samin Sirous; Arghavan Navadeh; Saeedeh Ebrahimgol; Faezeh Atri (Wiley, 2022)
Abstract Objectives This systematic review aims to investigate the effect of different preparation designs on the marginal fit and fracture strength of ceramic occlusal veneers. Materials and Methods Based on the PICO question and the search terms, an electronic search was performed in Google Scholar, PubMed (MEDLINE), Scopus, Cochrane Library, Web of Science, Science Direct, Wiley, Ovid, and SAGE for articles published up to July 2022. After including English in vitro studies that evaluated posterior ceramic occlusal overlays at the posterior with ceramic restorations by following the PRISMA statement, the extracted data was tabulated. The methodological quality of the included studies was evaluated. Risk of bias assessment was done independently by two authors using the modified MINORS scale. Results About 3138 search results were screened, of which 22 were selected due to their titles. Twenty‐one full‐text articles were assessed for eligibility. Seventeen in‐vitro studies were finalized for the extraction of quantitative data. All 17 articles had a low risk of bias and were retained. The influencing items for evaluating the research were different in most studies; therefore, qualitative synthesis of the results was feasible. They generally included preparation design, material thickness, depth of preparation in the tooth, internal divergence angle, and finish line. Meta‐analysis was not done due to heterogeneity of preparation types and evaluation methods. Results revealed that fracture resistance of occlusal veneers is higher than normal mastication force, and it is sufficient to prepare the occlusal surface, use a self‐etching primer for bonding, and an acceptable minimum ceramic thickness. The marginal discrepancy of occlusal veneers is clinically acceptable. However, this systematic review faces some limitations due to the lack of in vivo studies, different preparation designs in included studies, different follow‐ups, and lack of comprehensive explanations in articles. Conclusions The preparation design of occlusal veneers influences both marginal adaptation and fracture resistance. Various preparation designs are proven to have clinically acceptable fracture strength and marginal adaptation.